Challenging behaviours following paediatric acquired brain injury (ABI): The clinical utility for a manualised behavioural intervention programme. Issue 3 (19th August 2014) - Woods, Damith Thushara; Catroppa, Cathy; Godfrey, Celia; Giallo, Rebecca; Matthews, Jan; Anderson, Vicki A; McNicholl, Declan; Wicks, Beth
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose Children with acquired brain injury (ABI) are at significant risk of serious behavioural and social difficulties. The burgeoning growth of research documenting behavioural sequelae after paediatric ABI has not been met with a concomitant level of research aimed at treating the problem. The purpose of this study was to investigate whether a manualised behavioural intervention support programme, called 'Signposts', could (i) reduce challenging behaviours in children with acquired brain injury (ABI); and (ii) improve family-parental well-being and functioning. Design/methodology/approach Sixty-one parents (48 mothers and 13 fathers) of 48 children aged between 3 and 12 years with mild, moderate, or severe ABI received an ABI adapted 'Signposts for Building Better Behaviour' programme (Hudson et al., 2001) in group-support or telephone-support format. Trained 'Signposts' practitioners delivered the programme over a 5-month period. The programme consisted of nine information booklets, a DVD, and workbook. All families completed pre-intervention and post-intervention evaluations. Findings On average parents completed 7.92 out of a possible nine intervention sessions (range 7-9). Parents in both telephone-support and group-support formats reported significant reductions in challenging child behaviours irrespective of injury severity. They also reported significant reductions in dysfunctional parenting practices, stress and family burden. Originality/value Overall, the current research provides support for 'Signposts' to be used with families of children with ABI in an attempt to ameliorate negative outcomes for family, parent, and child.